EFFECTS OF LISTENING CONTENT ON STUDENTS’ LISTENING COMPREHENSION AS PERCEIVED BY FIRST-YEAR STUDENTS AT UET, VNU - Trần, Thị Thanh Vân (2021)
This study aims at investigating effects of the content of listening texts on EFL learners‟ listening comprehension. In detail, its main purpose is to identify the extent to what listening content affects students‟ comprehending in listening as perceived by first year students at UET, VNU. In addition, the reasons why listening content set barriers to students‟ comprehension was also exploited. A secondary aim of the paper is to come up with some suggestions to improve the situation. The findings from this present study are expected to be useful for both the students and the teachers of English. To achieve those goals, the research tries to answer the following questions: To what extents does content of listening texts affect students’ listening comprehension as perceived by first-year students at UET, VNU? Why does content of listening texts affect students’ listening comprehension as perceived by first-year students at UET, VNU?